Cytotoxic Effects of Ethanol Extract of Malaysia Indigenous Marine Microalga, Chaetoceros Calcitrans on Human Breast Canser Line MCF-7 - Nigjeh, Siyamak Ebrahimi (2011)
Algae are being used by millions of humans and animals around the world as nutritional or pharmaceutical ingredients due to their vast diversity, diverse chemical compositions and biological activities. In the current study, cytotoxic effects of Malaysian a marine microalga, Chaetoceros calcitrans were evaluated. Briefly, Chaetoceros calcitrans was identified and cultured. The Chaetoceros calcitrans ethanol extract (EEC) was screened using MTT assay for cytotoxicity on various human cancer cell lines, K562 (leukemia), HT29 (colorectal), HeLa (cervical), MCF-7 (breast) and also on normal cells, MCF10A (human normal breast cell) and PBMC (peripheral blood monolayer cell). Tamoxifen was used as a positive control. The mode of cell death induced by EEC was determined by Annexin V/PI followed by flow cytometry cell cycle analysis. The effects of EEC treatment on MCF-7 cells in expressions of apoptotic related genes, Bax, Bcl-2, BCL2L1, TNF, P53, Fas, Caspase3, Caspase7 and Caspase9 and cell cycle genes, P21Cip1, CyclinA2, CDK2 and MDM2 were determined using GeXP system, a multiplex quantitative gene expression technology. Overall, the EEC showed different IC50 values on the tested cell lines at different time points (24, 48 and 72 hours). The lowest IC50 value for MCF-7 (3.00±0.65 μg/ml) compared to that for MCF-10A cells (12.00±0.59 μg/ml) was obtained at 24 hour after treatment. Besides that the IC50 value of EEC on MCF-7 (3.00±0.65 μg/ml) was lower than the IC50 value of Tamoxifen (12.00±0.52). EEC was not cytotoxic towards PBMC even at its highest concentration. Hence, the EEC can be considered having anti cancer properties. Based on Annexin V/PI and cell cycle flow cytometry analysis, it was found that inhibition of cell growth by EEC on MCF-7 cells is through the induction of apoptosis without cell cycle arrest. The apoptotic cells at subG0/G1 phase in treated MCF-7 cells at 48 and 72 hours showed 34 and 16 folds increase compared to treated MCF-10A cells which showed only 6 and 7 folds increase at the same time points, respectively. The results from this study also showed that EEC induced apoptosis of MCF-7 cells without cell cycle arrest that is associated with the modulation of expression of selected cell cycle and apoptosis related genes such as MDM2, p21Cip1 as well as increasing the expression of pro-apoptotic protein Bax and decreasing the expression of the antiapoptotic protein Bcl-2. The EEC treatment on MCF-7 cells caused the fold changes of MDM2 to decrease from 1.8 at 6 hours to 1.4 at 24 hours; the fold changes of CyclinA2 also decreased from 3.5 at 6 hours to 1.5 at 24 hour whilst,the fold changes of p21Cip1 also increased from 0.8 at 6 hours to 1.9 at 24 hour. The EEC treated cells also modulate the fold changes of the key caspase molecules where the fold changes of caspase3 and caspase7 decreased from 1.5 and 2.1 at 6 hour to 1.3 and 2.0 at 24 hours, respectively. The Bax activation might have been involved in the release of cytochrome c from the mitochondria and clustered with APAF-1, a apoptotic protease activating factor 1 and resulted in activation of caspase9 (although it was not determined in the experiment) which then cleaved the downstream caspease3, 6 and 7 that lead to apoptosis. Hence, EEC induced apoptosis of MCF-7 cells associated with expression of several major regulators of the cell cycle such as CDK2, MDM2 and Cyclin A2 and apoptotic related genes by increasing in Bax/Bcl-2 ratio that in turn activate the caspase-dependent pathway. This study also showed that EEC could induce apoptosis through a caspase-dependent pathway by activating caspase3 and 7 in MCF-7 cells. Based on the results obtained from this study, it appears likely that EEC has the potential cytotoxic effect on breast cancer. However, more studies were required which include isolation, characterization and synthesis of the active compound (s) found in EEC that was associated with the strong apoptotic effects against breast cancer cells.